Llama - Arnold, Caroline; Hewett, Richard (New York : Morrow Junior Books, 1988)
Describes the characteristics and behavior of llamas and their usefulness to man, discusses other members of the lamoid family, and reports on the growing number of llamas now being bred in the United States.
Includes index.
Booklist.
Elem. School Library Collection.
Wilson's Children.
5.3
5.3.
Keywords: Lama (Genus) -- Juvenile literature; Llamas -- Juvenile literature; Lama (Genus); LLamas; Lama (Genus); Llamas